Gerenciamento da potência em painéis fotovoltaicos aplicados em conversores multiníveis conectados à rede elétrica - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work presents a study about the power management in photovoltaic panels as primary sources of multilevel converters connected to the grid, developed through simulations in the PSIM software. Firstly, a photovoltaic arrangement with a 3x3 configuration of series-parallel panels is modeled using the data of the photovoltaic module of the Kyocera KD210GX-LPU model. Afterwards, the components of a nonisolated Boost DC-DC converter are dimensioned in order to raise the voltage levels delivered by the proposed PV array. The converter operates with a maximum power point tracking algorithm (MPPT) integrated with its control. Among the existing MPPT methods, it was decided to develop an algorithm based on the Perturbation and Observation (P&O) method, which was implemented and simulated within a specific block of the PSIM (C Blocks). Finally, the developed photovoltaic system is integrated with an already designed multilevel system that works connected to the power grid, replacing a current source that represented such a set. Thus, through simulations, it was possible to verify the interaction of photovoltaic and multilevel systems, transferring to the grid the maximum instantaneous power generated by the panels.
Keywords: Engenharia elétrica; Energia solar; Conversores elétricos; Electrical engineering; Solar energy; Electric Converters; CNPQ::ENGENHARIAS